Pemanfaatan Lahan Bekas Pertambangan Emas Tanpa Izin (PETI) Di Desa Temenggung Kecamatan Limun Kabupaten Sarolangun - Diki Pernandes; M. Nazori; Ahmad Syukron Prasaja (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
The large number of ex-illegal gold mines in Setajo Raya Subdistrict which was caused by illegal mining activities made the former mining land abandoned by the miners and no longer used. The number of losses incurred from these PETI activities include: changes in the color of river water, damaged soil due to excavation, river pollution. Seeing the condition of the problems that exist in the District of Setajo Raya, a research was carried out on